Clinical-epidemiological Profile of Outpatients with Mild to Moderate Covid-19 Intensity, in the South of Mexico City - María de Lourdes Patricia Ramírez Sandoval; Alejandro Roldan Vences; Jorge Eduardo Macias Garza; Maribel Adriana Varela Ramirez (Current Progress in Medicine and Medical Research Vol. 9, 2023)
Objective: Report the clinical-epidemiological profile of outpatients with mild to moderate intensity COVID-19, which was carried out in the South of Mexico City. The data were obtained through a pre-coded questionnaire, designed only for this study, the identification card was taken and sociodemographic variables were measured, non-pathological personal history (transmission mechanism), pathological personal history (comorbidities diabetes mellitus, arterial hypertension, previous lung pathology, cancer, HIV, AIDS, asthma, allergy, obesity, cardiovascular disease, smoking, alcoholism) Current Condition, Signs and symptoms, laboratory and cabinet studies. Materials and Methods: This is a prospective, cross-sectional, observational, single-center study of a series of patients with clinical data of upper and lower respiratory tract infection and positive PCR for SARS-CoV-2. The study population consisted of 66 patients who met the inclusion criteria, carried out by telemedicine to a first contact office specializing in infectious diseases, attended from March 10, 2020 to January 31, 2021. The information was analyzed in a statistical package using SPSS 23.0. Results: 66 patients who met the criteria established for diagnosis were attended. The month of January 2021 saw the highest number of patients, who requested medical attention, 6.5 days (range 1 to 12 days) after starting the disease. The median age was 48 years (range 10 to 80 years), 53% were female, 26% had type 2 diabetes mellitus, 23% with arterial hypertension, 7% previous lung disease, 4% suffered from hypothyroidism, 24% positive smoking, 21% positive alcoholism, 39% had obesity, 17% were allergic. The clinical characteristics, the most prevalent was cough in 76%, followed by headache 73% and myalgia 71%. Conclusions: Patients with comorbidities, whether men or women in the fifth decade of life, are of great importance for the evolution, especially when they are carriers of immunosenescence in the cases of those over 60 years of age, or the immune system is immunocompromised as it is. the case of patients with DM2 and even more when they have more than one comorbidity that persecute have a proinflammatory state and attenuation of the innate immune response